Analisis Prosodi Semantik Kata-kata Bermakna ‘Talking a lot’ - Andiani Rezkita Nabu (LP2M IAIN Sultan Amai Gorontalo, 2020)
Due to sentence formation, the lexicon choice appears as a crucial phase of writing. Moreover, it is caused by the emptiness of words set that are perfectly synonymous and can be interchangeable. In order that it leads the needed for meaning, sense, and evocative value identification in the choice of the lexicon. Furthermore, the main objective of this research is to examine the value (sense) of several lexicons, which means 'talking a lot' such as talkative, loquacious, chatty, gossipy, garrulous, talky, and conversational, by using cognitive-linguistic and corpus linguistic approaches. In this case, the researcher examined the lexicon values based on the distinguishing semantic features and semantic prosody of the lexicons. As a linguistic corpus study, this study involved a number of data derived from COCA (Corpus of Contemporary American English), the Oxford dictionary (online), and the Merriam-Webster dictionary (online). Hence, this study found that the distinctive features of the lexicons are the subject, the object, the type of communication, the type of information, and the causes. Therefore, the semantic prosody in translation practices applies in corpus-based approach translation. It can facilitate a translator to comprehend new words and improve the quality of translation work.